ELEVATING SPEAKING SKILL THROUGH STICK PUPPET ROLE PLAY - YULI ASTUTI HASANAH (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2021)
This research was to describe how stick puppet role play can improve the students’ speaking skill in terms of fluency, grammatical accuracy, pronunciation and vocabulary in delivering conversations for the language functions of inviting, accepting or refusing invitation, complimenting, and congratulating someone. The design used was classroom action research. The researcher was the teacher of the class and was assisted by the observer to observe the implementation of the strategy. The research was conducted in one cycle for five meetings. The subjects of this research were thirty two students of VIII A class of SMP Laboratorium Universitas Negeri Malang, in the academic year of 2012/2013. The instruments of this research were observation checklist, speaking test for role play and questionnaire. In addition, the data were analyzed and reported descriptively. This research was considered successful if the average of the students’ speaking scores met the criteria of success at least 70 for the whole class. The procedures of the implementation of stick puppet role play cover five main steps, namely: modeling, drafting, creating, rehearsing, and performing. In modeling, the teacher modeled how to use the expressions of inviting, accepting or refusing invitation, complimenting, and congratulating someone through the use of videos and model of conversations. In drafting, the students made their own draft of conversations while in creating step, the students created the stick puppets based on the characters in the conversations. Furthermore, in rehearsing, the students practiced their performance of stick puppet role play while the teacher gave feedback for improvement. Finally, in performing, the students performed the stick puppet role play on the stage and recorded by the observer. The research finding showed that from thirty two students, twenty six students got fair, two students got good, four students got very good, and none got excellent. It means that thirty two students (100 %) could pass the criteria of success as the students’ scores were above 70. The students’ average score was 74. The highest score was 85 and the lowest was 70. Moreover, the implementation of the strategy also brought positive students’ attitude in the range of vocabulary, the ease of getting an idea, the speaking skill improvement, the students’ excitement, the students’ enthusiasm, the students’ confidence, and the effectiveness of the implementation of stick puppet role play. Therefore, suggestions are delivered to English teachers to use stick puppet role play in teaching speaking for not only other language functions such as agreeing and disagreeing but also to other genres such as narrative and descriptive. It is also offered to future researchers to conduct a study on the use of stick puppet role play to English receptive skills such as listening and reading as this study focused on speaking in which belongs to the productive skill.